Media Literacy and Social Awareness in Funeral Practices in the Digital Era - Zakiatul Abdi; Zukfi Akmal; Muhammad Yahya; Syamsudin Syamsudin; Sobri Sobri (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2026)
The rapid development of digital technology has significantly changed the way people access and interpret information. The abundance of digital information is not always accompanied by accuracy, potentially leading to misunderstandings. This study aims to analyze the role of media literacy in fostering social awareness regarding funeral practices in the digital era. This research used a qualitative approach with a phenomenological method and was conducted in Ampangan District, Payukumbuh. Data were collected through in-depth interviews with informants, participant observation, and documentation of digital content. Data validity was ensured through source triangulation and member checking. The findings indicate that media literacy enhances individuals' ability to critically evaluate information, strengthens social participation, and reinforces collective responsibility in cemetery management. However, challenges such as misinformation, reduced in-person social interaction, and the commercialization of funeral services remain significant. This study highlights the importance of integrating media literacy into community education and involving religious leaders in disseminating accurate information. These findings contribute to the development of socio-religious communication studies and offer practical implications for strengthening community-based media literacy programs.